تطوير مواد المحاورة على أساس الثقافة المحلية بالتطبيق على الطلبة في المدرسة لقمان الحكيم الابتدائية جمبر: Development of Local Culture-Based Conversation Materials for Luqman Al-Hakim Elementary School Students Jember. Thesis. Arabic Language Education, Postgraduate, Kiai Haji Achmad Siddiq State Islamic University Jember - Dzawil Albab; Surahmat Surahmat (Postgraduate Study Programme of Universitas Islam Negeri KH. Achmad Siddiq Jember, Indonesia., 2023)
Luqman Al-Hakim School is a school under the auspices of the Hidayatullah Foundation that uses “Al Muhawarah Lil Mubadiin” teaching materials. The teaching materials used in grade 5 are not by the objectives of learning Arabic because Arabic teaching materials must include four skills, and these teaching materials do not have material related to speaking skills except evaluation-based, making it difficult for students to learn. Based on these problems, the researchers raised the focus of research on 1) the design of teaching materials, 2) the Validity of teaching materials, and 3) how effective the use of teaching materials. This study aims to produce teaching materials entitled “Al Muhawarah Lil Mubadiin” based on local culture so that the learning process runs effectively and becomes a solution to the problems above. This research includes Research and Development (R&D) with the ADDIE model for data collection using observation techniques, interviews, questionnaires, and documentation. The data sample is all students of class V. The product trial uses qualitative and quantitative. In qualitative, researchers have obtained data on the effectiveness of students, which were then tested with the Cronbach Alpha formula, Product Moment, questionnaire data analysis, and the coefficient of determination. The results of this study were obtained: 1) The product design was designed using Photoshop CS6 and Microsoft Word 2010. 2) Based on the results of product feasibility tests by design experts with a value of 90% and from material experts with a value of 94% with very feasible criteria. 3) The results of product trials with a coefficient of determination resulted in the effectiveness of the product being 87.80%, determined by the conversation material, and the remaining 12.20% estimated from other factors.